The Selection of Weapon Systems in The A2/AD (Not Access/Area Denial) Strategy at Indonesia's Strategic Choke Points by Using The Analytical Hierarchy Process (AHP) Method - Tri Yudha Ismanto; Fathurrohman Umar; Setyanggono Eko Lutvie; Udayana Agung; Prasetyo Hari; Midhio I Wayan; Yusgiantoro Purnomo (Publikasi Indonesia, 2024)
This article utilizes the Analytical Hierarchy Process (AHP) method to decide how to choose an effective weapon system for the A2/AD (anti-access/area denial) strategy at the Sunda Strait, Indonesia's strategic choke point. The main discussion is limited to selecting the types of weapon systems considered effective in implementing A2/AD at Indonesia's strategic choke points. The next step is to decide which primary, secondary, and alternative criteria are the most important. Each of these will then be put together mathematically by measuring consistency using the Consistency Index (CI), the Consistency Ratio (CR), and the Consistency Hierarchy, which is the ranking as the result of the analysis. This method resulting in a weight for the navigation criteria of 66%, projection of 19%, and operability of 16%. Furthermore, in conclusion, the order of the best weapon systems is RBS15 MK4 with a weight of 66%, Brahmos II at 18%, and Neptune 360ST at 16%.